Black against empire : the history and politics of the Black Panther Party - Bloom, Joshua; Martin, Waldo E., 1951- (University of California Press : University of California Press, 2016)
This timely special edition, published on the fiftieth anniversary of the founding of the Black Panther Party, features a new preface by the authors that places the Party in a contemporary political landscape, especially as it relates to Black Lives Matter and other struggles to fight police brutality against black communities. In Oakland, California, in 1966, community college students Bobby Seale and Huey Newton armed themselves, began patrolling the police, and promised to prevent police brutality. Unlike the Civil Rights Movement that called for full citizenship rights for blacks within.